OCCURRENCE AND COMPOSITION OF FORAGER AND CARNIVORE FISHES IN IVO RIVER SOUTHEAST NIGERIA - OYEDIRAN, A. G; UCHE, F. O.; OLAOTI, K. S.; OKE, D, R. C.; UMAN, I.; UDOFIA, C. T.; NWAFOR, S. E. (Nigerian Journal of Fisheries, 2021)
Studies on occurrence of forager and carnivore fish composition in Ivo River Southeast Nigeria were carried out. A total of 54 individuals were collected representing 12 species and 8 families. Three stations 1 (upstream Ivo River), 2 (Ivo Dam), and 3 (downstream Ivo River) were selected. Station 2 recorded 32 individuals with 0.33 F/C while in Stations 1 and 3, there were 12 individuals with 0 F/C and 10 individuals with 0.25 F/C respectively. Cichlidae dominated the fish family with 35.1% while alestidae (20.4%)> clarotidae (12.9%)>schilbeidae (11.1%)>hepsetidae (9.2%)>clariidae (7.5%) and cyprinidae and mormyridae constituted 1.9% each. Shannon- Weiner diversity indices (H) was highest in Station 2 (H=2.182) and lowest in Station 3 (H=1.609). Ivo River had a low fish abundance and diversity while the occurrence of carnivorous fish was more than foragers, this showed an unbalanced fish population in all the stations. The impoundment in station 2 along with the different anthropogenic activities and the feeding relationship could be implicated for the unbalanced fish population. Hence an immediate sustainable restoration approach should be put in place to conserve and establish a balanced fish population in Ivo River.